2007
DOI: 10.1161/atvbaha.107.152629
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis Is Attenuated by Limiting Superoxide Generation in Both Macrophages and Vessel Wall Cells

Abstract: Objective-We previously showed that NAD(P)H oxidase deficiency significantly reduces atherosclerosis in apoE Ϫ/Ϫ mice. The present study was designed to determine the relative contribution of monocyte/macrophage versus vascular wall cell NAD(P)H oxidase to atherogenesis in this model. Methods and Results-Cell-specific NAD(P)H oxidase inhibition was achieved via allogenic, sex-mismatched bone marrow transplantation. Aortic atherosclerosis and superoxide production in apoE Ϫ/Ϫ mice (Control) with functional NAD(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
129
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(138 citation statements)
references
References 37 publications
(42 reference statements)
6
129
1
Order By: Relevance
“…Total aortic plaque surface area decreased as shown, but no decrease was seen in aortic sinus plaque (113). Bone marrow-derived and vascular wall cells appear to make equal contributions (1872). Also required for NF-B signaling by TNF␣ (and others) (1026).…”
Section: %mentioning
confidence: 73%
See 1 more Smart Citation
“…Total aortic plaque surface area decreased as shown, but no decrease was seen in aortic sinus plaque (113). Bone marrow-derived and vascular wall cells appear to make equal contributions (1872). Also required for NF-B signaling by TNF␣ (and others) (1026).…”
Section: %mentioning
confidence: 73%
“…In bone marrow transplant studies in ApoE-deficient mice, deficiency of p47 phox in the artery wall with normal bone marrow resulted in a 66% reduction in atherosclerosis and marked reduction of VCAM-1, ICAM-1, and P-selectin adhesion molecules expressed on both endothelial cells and VSMC as well as relative insensitivity to thrombin signaling. Transplant of p47 phox -defective, ApoE-deficient marrow into ApoE-deficient mice with wild-type p47 phox resulted in 53% attenuation of atherosclerosis, suggesting both vascular wall and macrophage production of superoxide contributes importantly to atherosclerosis progression (1872).…”
Section: Signaling Cassettes Activated By Rtk Are Mutually Supportivementioning
confidence: 99%
“…32 Fresh-frozen sections of RPE-choroid were prepared from eye cups as described above. Control and experimental sections were placed on the same slide and processed under the same conditions.…”
Section: Ros Detection In Retina/choroid Sectionsmentioning
confidence: 99%
“…These mice are hypercholesterolemic and spontaneously develop atherosclerotic plaques in the aorta and arterial branches thereof. Three previous studies have directly investigated the role of NADPH oxidases in atherogenesis in ApoE Ϫ/Ϫ mice through the genetic deletion of p47 phox (i.e., via generation of p47 phoxϪ/Ϫ /ApoE Ϫ/Ϫ double knockouts) (3,14,28). These studies indicated that, although p47 phox expression may not contribute to lesion development in the aortic sinus of ApoE Ϫ/Ϫ mice, it plays a major role in atherogenesis in the descending aorta, with the deletion of p47 phox resulting in up to an 80% smaller lesion area.…”
mentioning
confidence: 99%